DNA sequence selectivity of guanine-N7 alkylation by nitrogen mustards. - Mattes, W B (1986)
Nitrogen mustards alkylate DNA primarily at the N7 position of guanine. Using an approach analogous to that of the Maxam-Gilbert procedure for DNA sequence analysis, we have examined the relative frequencies of alkylation for a number of nitrogen mustards at different guanine-N7 sites on a DNA fragment of known sequence. Most nitrogen mustards were found to have similar patterns of alkylation, with the sites of greatest alkylation being runs of contiguous guanines, and relatively weak alkylation at isolated guanines. Uracil mustard and quinacrine mustard, however, were found to have uniquely enhanced reaction with at least some 5'-PyGCC-3' and 5'-GT-3' sequences, respectively. In addition, quinacrine mustard showed a greater reaction at runs of contiguous guanines than did other nitrogen mustards, whereas uracil mustard showed little preference for these sequences. A comparison of the sequence-dependent variations of molecular electrostatic potential at the N7-position of guanine with the sequence dependent variations of alkylation intensity for mechlorethamine and L-phenylalanine mustard showed a good correlation in some regions of the DNA, but not others. It is concluded that electrostatic interactions may contribute strongly to the reaction rates of cationic compounds such as the reactive aziridinium species of nitrogen mustards, but that other sequence selectivities can be introduced in different nitrogen mustard derivatives.